2016
DOI: 10.1016/j.physbeh.2016.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Mayflies are least attracted to vertical polarization: A polarotactic reaction helping to avoid unsuitable habitats

Abstract: Like other aquatic insects, mayflies are positively polarotactic and locate water surfaces by means of the horizontal polarization of water-reflected light. However, may vertically polarized light also have implications for the swarming behaviour of mayflies? To answer this question, we studied in four field experiments the behavioural responses of Ephoron virgo and Caenis robusta mayflies to lamps emitting horizontally and vertically polarized and unpolarized light. In both species, unpolarized light induces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 19 publications
1
19
0
1
Order By: Relevance
“…During their compensatory flight, the females use their polarization sensation to follow the horizontally polarizing track of the river. However, when they encounter a bridge or riverside, the horizontally polarized signal of the river is interrupted by the vertically polarized mirror image of the bridge or riparian vegetation [ 22 , 25 , 38 ]. Hence, the bridge as an optical barrier is able to interrupt the compensatory flight of both diurnal and nocturnal mayflies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During their compensatory flight, the females use their polarization sensation to follow the horizontally polarizing track of the river. However, when they encounter a bridge or riverside, the horizontally polarized signal of the river is interrupted by the vertically polarized mirror image of the bridge or riparian vegetation [ 22 , 25 , 38 ]. Hence, the bridge as an optical barrier is able to interrupt the compensatory flight of both diurnal and nocturnal mayflies.…”
Section: Discussionmentioning
confidence: 99%
“…Several anecdotes, press reports and case studies have showed that illuminated boats and lamplit bridges overarching a river are major threats to nocturnal mayfly populations, like Ephoron virgo (Olivier, 1791) [ 22 ]. Huge mayfly swarms around illuminating street lamps were observed on the river Danube [ 22 25 ], Mississippi [ 26 ], Rhine [ 27 ], Main [ 28 ], at the Ardahan bridge on Kura river [ 29 ], bridge of Tudela on Ebro river [ 30 ] and bridge of Route 462 over the Susquehanna river, Pennsylvania [ 31 ]. According to Száz et al .…”
Section: Introductionmentioning
confidence: 99%
“…This mixing of the two components results in the decrease of the degree of polarisation. In cases, when the vertically polarised component overwhelms the surface-reflected light (e.g., when direct sunlight illuminates the water), the total water-returned light can be vertically polarised (Farkas et al 2016) as shown in Figures 2a-c. Thus, the angle of polarisation  of creek-reflected light depends on sunlight and shade conditions.…”
Section: Discussionmentioning
confidence: 99%
“…One fly species, Halaeomyia petrolei even became adapted to a life near (or in the case of its larvae/pupae: inside) naturally occurring petroleum pools, feeding on arthropod prey that became trapped there (Thorpe, 1930 ). Female mayflies were shown to use horizontally polarized reflections off water to direct their so-called “compensatory upstream flights” before oviposition (Farkas et al, 2016 ) and this dispersion behavior is disrupted by (unpolarized) light pollution, for instance illuminated bridges (Szaz et al, 2015 ). In another example, female dragonflies attempted to lay eggs on an artificial, horizontally polarized surface, assuming it to be water (Wildermuth, 1998 ).…”
Section: Behavioral Responses Of Different Insect Species To Reflectementioning
confidence: 99%